Analisis Keuntungan dan Kelayakan Ekonomi Usahatani Tembakau Virginia di Kabupaten Lombok Tengah - Nursan, Muhammad; Ayu, Candra; Suparyana, Pande Komang (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
Virginia tobacco is one of the most cultivated plants by farmers on Lombok Island, one of which is in the Central Lombok Regency. Virginia tobacco farming is one source of farmers' income because the income generated is quite high. Therefore, the purpose of this research is to find out the benefits of Virginia tobacco farming in Central Lombok Regency and to analyze the economic viability of Virginia tobacco farming in Central Lombok Regency. This research using a descriptive research method, and it was conducted in Janapria District, Central Lombok Regency, which was selected by purposive sampling with consideration of the area with the highest area and number of Virginia tobacco farming production. Data sources in this study include primary data and secondary data. Primary data was collected by a survey method of 30 respondents, where the selection of respondents is done by accidental sampling techniques. Data analysis in this study uses economic feasibility analysis including R/ C ratio and B / C ratio analysis. The results showed that the average profit of Virginia tobacco farming is Rp.42,349,763/hectare and Virginia Tobacco Farming in Central Lombok Regency is economically feasible because it has an economic viability value of R/C ratio of 1.9 and B/C ratio of 0.9.